Tearing Plato to Pieces: Gianfrancesco Pico della Mirandola and Marsilio Ficino on the History of Platonism. - ROBICHAUD, DENIS J.-J. (Renaissance & Reformation / Renaissance et Réforme)
This article considers Gianfrancesco Pico della Mirandolos understanding of the history of Platonism in his Examen vanitatis. It analyzes his sources and methods for understanding the history of philosophy--genealogical source criticism, historiographical analysis, and comparative history-- and argues that his approach is shaped by anti-Platonic Christian apologetics. It documents how Gianfrancesco Pico closely studies Marsilio Ficino's and his uncle Giovanni Pico's understandings of Platonism and its history, and how his contextualization of their work within the broader history of Platonism is part of a larger endeavour to turn the page and even close the book on this chapter of the Quattrocento. Although neither Ficino nor Gianfrancesco finds universal agreement among ancient Platonists, Ficino explains their history as one of inquiry and interpretation, in which Platonism and Christianity are inexorably united, whereas Gianfrancesco characterizes it as a history of lies and disagreements that threaten Christianity In trying to protect sacred history, Gianfrancesco Pico helped develop the tools that would eventually critique it.